Effect of High Plane of Nutrition on Blood Biochemical Profile and Onset of Puberty in Prepubertal HF X Kankrej Crossbred Heifers - Hadiya, KK; Dhami, AJ; Chaudhari, DV; Lunagariya, PM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This study was initiated on 24 prepubertal Holstein x Kankrej crossbred heifers of nearly identical age (7-9 months) and body weight  (130–140 kg) at University farm to evaluate the effect of high plane of nutrition on blood biochemical and minerals profile and the age  at puberty. Twelve heifers were managed under routine farm feeding (control) and the rest 12 under ideal optimum feeding regime  (treatment) that included extra 1 kg concentrate, 30 g min mix and ad-lib dry fodder. The body weight and ovarian ultrasonography  together with blood sampling was carried out at monthly interval from 10–18 months of age to study the ovarian dynamics and blood  biochemical changes. High plane of nutrition to growing heifers was beneficial in reducing the age of onset of puberty (by 2–3 months)  compared to routine farm fed group. The mean plasma total protein and cholesterol concentrations showed a rising trend with significant  variations from 10 to 16 months of age, where it got mostly stabilized indicating adult profile. The activity of enzymes GOT and GPT also  rose gradually and significantly from 10 months till 14–15 months of age, and thereafter it remained more or less static till 18 months of  age. The levels of both these enzymes were higher, with lower protein and cholesterol, in control than the treatment group from 15–16  months of age onwards. The mean plasma levels of both calcium and phosphorus increased gradually and significantly with advancing  age till 16–17 months of age, with little higher values in supplemented than a control group. The plasma levels of zinc, iron, copper, and  cobalt also showed rising trend with significant differences between 10th and 12th–14th months of age, and from 15th–18th months of  age the levels were statistically the same in all the groups with slightly higher values in the treatment group.
Keywords: Age at puberty; Blood biochemical profile; Crossbred heifers; Plane of nutrition